2012
DOI: 10.1007/s13520-012-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

Women on board, firm financial performance and agency costs

Abstract: This study investigates the link between female board directors and company financial performance and agency costs in Sri Lanka's publicly listed companies. In order to investigate the impact of board gender diversity on firm financial performance, a dynamic panel generalised method of moment estimation is applied. Three variables are used as proxies for gender diversity of the board of directors, namely the percentage of women on the board, a dichotomous dummy and the Blau index. A Tobit model with endogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 31 publications
3
32
1
1
Order By: Relevance
“…The argument for this is that bigger firms may be too tough for females. In another study in Sri Lanka by Wellalage and Locke (2013), it is realized that females' representation on top management has significant negative relationship with firm value. They attribute the negative relationship to an agency cost imposed by diversity in board.…”
Section: Empirical Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The argument for this is that bigger firms may be too tough for females. In another study in Sri Lanka by Wellalage and Locke (2013), it is realized that females' representation on top management has significant negative relationship with firm value. They attribute the negative relationship to an agency cost imposed by diversity in board.…”
Section: Empirical Reviewmentioning
confidence: 98%
“…In spite of the arguments in favour of female inclusion in top management of organisations, empirical studies have been very mixed in their findings on the relationship between females in top management and firm performance. While a host of studies have concluded that female in top management results in high firm performance, (see: Dezsö & Ross, 2012;Reinert et al, 2016;Faccio et al, 2016;Wu et al, 2017;Moreno-Gómez et al, 2018), other studies have established a negative relationship between female in top management and firm performance (see: Darmadi, 2013;Ryan & Haslam, 2005;Ujunwa, 2012;Wellalage & Locke, 2013). Apart from these two groups of contrary findings, other studies have findings that suggest that females in top management have no influence on firm performance (see: Cabrera-Fernández et al, 2016;Pletzer et al, 2015;Ming & Eam, 2016;Marinova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Agency approach also argues that females on boards might monitor management team (Carter, D'Souza, Simkins, & Simpson, 2010), reducing information asymmetries and agency costs (Wellalage & Locke, 2013 (Byrnes, Miller, & Schafer, 1999), bring different perspectives to the boardroom, and develop a more trusting leadership style than men (Trinidad & Normore, 2005). Therefore, the presence of female directors on boards reduces opportunistic behaviors and exercises greater control over CEO pay.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…They are characterized by being obedient and sensitive. These different traits have resulted in different types of response to corporate policy and regulation by women and men 4 . The existence of CEOs is crucial in corporate governance, since they are in charge of coordinating all the activities of boards in firms.…”
Section: Gender Diversitymentioning
confidence: 99%